The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11239-011-0607-4
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary thromboembolism in an East African tertiary referral hospital

Abstract: Pulmonary thromboembolism (PTE) is a frequent cause of mortality in Kenya, but its characteristics are hardly reported in Subsaharan Africa. To describe the pattern of PTE among black Africans, in a Kenyan referral hospital. Retrospective study at Kenyatta National Hospital (KNH), Nairobi, Kenya. Records of patients seen between January 2005 and December 2009 were examined for mode of diagnosis, comorbidities, age, gender, treatment and outcome. Data were analyzed using SPSS version 15.0 and are presented in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 23 publications
6
24
0
Order By: Relevance
“…The male predominance this study is similar to the 55% reported by Kingue et al in Yaoundé-Cameroon [17], and different from that reported by that reported by Ogeng'o et al at an East African tertiary referral hospital [6]. The mean age of or patients was lower than the 60 ± 11.7 years reported by Aissa et al [7] in Tunisia, but higher that reported by Kingue et al [17] and Ogengo'o et al [6], who reported a mean age of 46 and 40.8 years respectively.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The male predominance this study is similar to the 55% reported by Kingue et al in Yaoundé-Cameroon [17], and different from that reported by that reported by Ogeng'o et al at an East African tertiary referral hospital [6]. The mean age of or patients was lower than the 60 ± 11.7 years reported by Aissa et al [7] in Tunisia, but higher that reported by Kingue et al [17] and Ogengo'o et al [6], who reported a mean age of 46 and 40.8 years respectively.…”
Section: Discussionsupporting
confidence: 54%
“…The mean age of or patients was lower than the 60 ± 11.7 years reported by Aissa et al [7] in Tunisia, but higher that reported by Kingue et al [17] and Ogengo'o et al [6], who reported a mean age of 46 and 40.8 years respectively. [3].…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…PTE diagnosis represented 0.31% of all hospitalizations during the 2-year studied period, an incidence rate similar to those reported in the United States (between 0.047-0.40%) [7]. Our data is limited to PE patients who were hospitalized, and PTE diagnosis could be more frequent in the emergency department, even though admittance rates reported in the US are around 86% [8].…”
Section: Discussionsupporting
confidence: 74%
“…Pulmonary Emboli occur in 23 to 107 per 100,000 residents in France [4]. There are limited epidemiologic data in Africa, and the majority of authors estimate the hospital incidence to be 1.2% to 3.1% [5,6,7,8]. In 2014, thromboembolic diseases were the second cause of hospital admissions for cardiovascular diseases, after heart failure in the cardiology service in Burkina Faso.…”
Section: Introductionmentioning
confidence: 99%